Alteration of Carotenoid Metabolic Machinery by β-Carotene Biofortification in Rice Grains - Ku, Hyung-Keun; Jeong, Ye Sol; You, Min Kyoung; Jung, Young Joo; Kim, Tae Jin; Lim, Sun-Hyung; Kim, Jae Kwang; Ha, Sun-Hwa (Journal of plant biology = Singmul Hakhoe chi, 2019)
To increase nutritional values as dietary sources of provitamin A and health-promoting antioxidants in rice grains, carotenoids have been biofortified in a Golden Ricelike variety, the stPAC ( stPsy-2A-stCrtI ) rice. In both of non-transgenic (NT) and stPAC seeds, total chlorophylls and carotenoids were gradually decreased during seed development while de novo biosynthesized carotenoids being comprised mainly of β-carotene, lutein and zeaxanthin were accumulated from early stage of 10 DAF and peaked at 20 DAF in stPAC seeds. The de novo production of carotenoids coincided with the high levels of transgene expression driven by the rice globulin gene promoter. Interestingly, expression levels of endogenous carotenoid metabolic pathway genes were the highest at 30 DAF in NT seeds whereas they were generally down-regulated in stPAC seeds, suggesting a negative feedback control mechanism of carotenoid metabolism by enhanced carotenoid production. The transgenic protein levels in stPAC seeds were not changed much during seed storage for up to 5 years, while carotenoid contents in the seeds were decreasing after 1 year of storage. The decrease in carotenoid contents was restored when the transgenic plants re-grown, supporting the reliability of transgenic pathways for carotenoid biofortification in rice grains. Thus, our results showed that transgene-driven biofortification of carotenoids was made and maintained over several transgenic generations with a possible negative feed-back control of endogenous carotenoid metabolism during seed development.